Studi Pengaturan Sistem Proteksi Undercurrent pada Penyulang Interkoneksi Industri di PLN Sumatera Selatan - Ayu Mawadda Warohma Warohma (Fakultas Teknik Universitas Lampung, 2026)
The interconnection between industrial power systems and the PLN distribution network improves supply reliability but also introduces potential abnormal operating conditions, such as loss of load due to the sudden disconnection of large industrial loads. This condition does not generate fault current and therefore cannot be detected by conventional overcurrent or earth-fault relays. This study discusses the application of an undercurrent relay (ANSI 37) as an additional protection scheme to detect loss of load conditions on an industrial interconnection feeder in the South Sumatra region. The research methodology includes analysis of the existing system conditions, determination of undercurrent relay settings, configuration of a Siemens Reyrolle 7SR10 relay, and testing using the secondary current injection method. The test results show that the undercurrent relay operates reliably when the current falls below the set value and does not misoperate under normal operating conditions. The results of this study are recommended as an effort to improve the reliability of the PLN distribution system and to strengthen electrical safety (K2) and occupational health and safety (K3) aspects.